The Role of Cultural Preservation Centre Region X in Preserving and Marketing Sambisari Temple to Increase The Number of Tourist Visits - Simangunsong, Kartika Theresia; Anggraini, Meisya (Politeknik Pariwisata NHI Bandung, 2025)
The Yogyakarta Cultural Heritage Conservation Centre is one of the agencies that has a role in the development and marketing of Sambisari Temple, which is one of the temple tourism destinations in Sleman Regency, Yogyakarta. This research was conducted to determine the development and marketing of the attractiveness of the Sambisari Temple Tourism Object and to find out the efforts made by the Yogyakarta Cultural Heritage Conservation Centre to make these attractions as cultural tourism objects that tourists are interested in in order to increase the number of tourist visits. This research was conducted using a direct data collection system by conducting interviews with parties managing objects and documents obtained from agencies involved in the tourism development process in Sleman Regency. The analysis technique used is descriptive qualitative data analysis technique, because descriptive data is data that describes the state of the object at the present time. The results of this study indicate that the role of the Yogyakarta Cultural Heritage Conservation Centre has been very good in the development and marketing of Sambisari Temple. In developing the Sambisari Temple Tourism Object, it turns out that there are still various problems, including the lack of supporting infrastructure for the Sambisari Temple Tourism Object. Key words: Preservation, Marketing, Culture